USE OF FAST IN EVALUATING UNDERGRAD STUDENTS' ATTITUDES TOWARDS HEALTH RULES DURING THE PANDEMIC (Brazilian Journal of Behavioral and Cognitive Therapy, 2025)
The Function Acquisition Speed Test (FAST) is a tool used to quantify stimulus relations. The objective of this study was to verify if FAST is effective in measuring implicit attitudes for public health behaviors involved in coronavirus pandemic in Brazilian undergrad students. Also, verify if Fast measures would have correlation with self-report measures. The 42 participants completed a trial block consistent with the guidelines of the World Health Organization (WHO) and another inconsistent. The results showed that 24 participants had a positive FAST effect, as they demonstrated faster learning in the consistent block and that most of these participants also indicated to be in accordance with sanitary rules, suggesting that FAST seems sensitive to quantifying relations between stimuli related to health care.
Keywords: covid-19; verbal learning; FAST; implicit attitudes